Analysis on Transient Contact Performance of Meshing Transmission of Cycloid Pin Gear in Robot Precision Reducer - Xuetao Qiao; Ke Jia; Chunshan Chen; Changlu Wang; Leyu Wei; Liyong Zhang; Weigong Wang (Jixie chuandong, 2021)
Transmission accuracy and dynamic stability of industrial robots precision reducer depend on the meshing performance of cycloid pin gear to a great extent. Therefore， 3D parametric modeling and transient dynamics analysis are carried out on the meshing transmission part of cycloid pin gear in the second stage of the precision reducer through the digital design and dynamics analysis platform combined with Creo and ANSYS Workbench， the model of precise reducer parameter and the stress and strain nephogram of cycloid pin gear tooth surface during dynamic meshing of cycloid needle wheel can be obtained quickly and accurately， thus the contact stress distribution law of cycloid and pin wheel in meshing process is obtained. The theoretical calculation results of Hertz contact theory are compared with the above simulation results， the correctness of the model is verified， which provides the necessary theoretical basis for the cycloid gear tooth profile optimization and modification.